Design and Performance of Two Axes Solar Tracker (Journal of Solar Energy Research Updates, 2017)
The possible energy gain in the case of two axes tracking as well as a fixed system with Equator facing tilted solar PV module with latitude angle and daily optimum slope is calculated basing on Hottel clear sky radiation model (HM) and ex-terrestrial solar radiation model (ESRM). The calculated results are compared with the data obtained from a PV system with 252 Wpeak power module installed on a two axes solar tracker which was designed and constructed locally. The main components of the tracker are introduced. It was found that, the maximum possible energy gain calculated basing on HM and ESRM are practically identic. For example, on 25 August from 8 O’clock to solar noon, the hourly energy gain values of HM are 1.672, 1.336, 1.170, 1.098 and 1.097 while they are 1.677, 1.337, 1.170, 1.098 and 1.098 in the case of ESRM. The corresponding measured values on the same day are 1.746, 1.36, 1.16, 1.043 and 1.027. Thus, the theoretical data are consistent with the measured ones. Moreover, it was found that the tracked system is more economic feasible than latitude tilted similar one with a relative solar energy gain of 0.32%.